Exploring the Intersection of Multicultural Society and Chicken Tikka Masala in the U.K. (OCEM Journal of Management, Technology & Social Sciences, 2024)
Chicken Tikka Masala is the national food of the U.K., which is considered to enhance as improving multicultural society in the U.K. This research explores the influence of national food (Chicken Tikka Masala) on multicultural society in the U.K. through a quantitative study involving two hundred and five participants, surveyed online. Factors reduction method was applied to group similar variables to produce principal components. Using principal component analysis and binary logistic regression, the research identifies a positive association between CTM’s cultural fusion and its contribution to a harmonious culinary fusion, positively impacting multicultural society in the U.K. However, no significant association is found between harmonious culinary fusion by CTM and its impact on multicultural society. The study highlights a noteworthy correlation between the expression and celebration of cultural backgrounds and the positive impact of CTM on enhancing multicultural society. Additionally, there is an association between cultural exchange, culinary creativity, and CTM’s impact on fostering multicultural society. Furthermore, the research underscores the significance of CTM in enriching multicultural society in the U.K., emphasizing the intricate association between food, culture, and societal harmony. The study highlights the need for a thoughtful cultural appreciation and preservation approach in the centre of culinary and cultural evolution. Overall, the examination of the intersection between multicultural society and Chicken Tikka Masala provides valuable insights into the cultural, social, economic, and identity-related dimensions of this widely celebrated dish, illustrating its power to bridge divides, create economic opportunities, and contribute to the cultural highlights of the nation.